ANALISIS KANYOUKU DALAM UNSUR TUBUH DADA (MUNE) PADA MEDIA SOSIAL X - Isnaeni, Indri; Natalia, Ana (Jurnal Bahasa Jepang Taiyou, 2024)
This study analyzes Japanese idioms that incorporate the body part "chest" (mune), focusing on structural classification, meaning, and usage in daily life. The research employs a qualitative descriptive method. Data were obtained from the social media platform X and Garrison's book on Japanese idioms. The classification of kanyouku is divided into two types: doushi kanyouku (verb-based idioms) and keiyoushi kanyouku (adjective-based idioms). Lexical and idiomatic meanings are categorized into four groups: emotions and sensory perception, physical and emotional states, actions, and character traits. The analysis of idiomatic expressions on social media X reveals the frequent use of idioms such as mune ga itamu ("the chest hurts") and mune ga ippai ni naru ("the chest becomes full"), which appear in various social, physical, and psychological contexts.